Potential Role of Extracellular Matrix and its Components in Cancer Development and Progression - Khan, Kahkashan; Afifa; Muhammad Imran; Nimrah Farooq (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
Cancer occurs due to unregulated multiplication of cells. Extracellular matrix (ECM) proteins come in a huge variety, and each one has unique biochemical and biophysical characteristics that affect the phenotype of cells. To ensure tissue homeostasis, the ECM undergoes continuous deposition, remodeling, and degradation from early development until maturity. In order to govern cell behavior and differentiation, the ECM's composition and structure are spatiotemporally controlled. However, when ECM dynamics are dysregulated in any way, illnesses like cancer can arise. Collagen is a major component involved in ECM regulation but after cross linking with each other, it initiates ECM stiffness, loss of cell contacts and cell geometry. Due to which most of the regulators including the Transcriptional coactivator with PDZ-binding motif (TAZ) and Yes-associated protein (YAP) are inhibited and cause extensive cell proliferation and tumor metastasis. Proteases like Metalloproteinases degrades collagen and other proteins that leads to ECM break down and cancer progression. As cancer spreads, the stress and pressure on cells increases which damage arteries and capillaries causing hypoxia. Hypoxia inducible factors take advantage of the situation and enhance invasiveness of cancer cells. This stress generated by tumor cells in their surrounding causes dysregulation of ECM matrix. Finding strategies to study the relationship between mechanical stress in tumors and their destructive behavior is vital for cancer research.